"The million dead, too, summ'd up" Walt Whitman's Civil War writings - Whitman, Walt 1819-1892 (University of Iowa Press, 2021)
"This book is the first to offer a comprehensive selection of Walt Whitman's Civil War poetry and prose with a full commentary on each work. One of the most distinguished critics in Whitman Studies, Ed Folsom, and one of the nation's most prominent writers and literary figures, Christopher Merrill, carry on a dialog with Whitman (and with each other), selection by selection, as they invite readers to enter into the conversation about how Whitman's writing about the Civil War develops, shifts, and manifests itself in different genres throughout the four years of the war. Folsom and Merrill go beyond Whitman's well-known war poems in his Drum-Taps and examine with equal care his Civil War prose writing in Memoranda During the War and in his personal letters.
Keywords: Whitman, Walt -- 1819-1892; Sezessionskrieg -- 1861-1865, Motiv; Whitman, Walt / 1819-1892 / Diaries; United States / History / Civil War, 1861-1865 / Poetry; United States / History / Civil War, 1861-1865 / Personal narratives; United States / History / Civil War, 1861-1865 / Literature and the war; Civil war in literature; Whitman, Walt / 1819-1892 / Criticism and interpretation; Whitman, Walt / 1819-1892; War and literature; United States; 1861-1865; Criticism, interpretation, etc; Diaries; History; Personal narratives; Poetry